Perancangan Dan Pembuatan Website Order Barang Parfumku.net - Kurniawan, Lucky; Rostianingsih, Silvia; Dewi, Lily Puspa (Jurnal Infra, 2015)
Parfumku.net is an online-based company engaged in the service order and delivery of perfume. Business processes owned by parfumku.net today still use the short message service (SMS) media to serve the order and delivery of perfume. Therefore, parfumku.net want to create a website that facilitates the customer to select and purchase the desired perfume, as well as enable the company to serve existing purchases.Website created a variety of features, in accordance with the access rights owned by the user, the admin or customer. Features - features that are owned by users who have access rights as a customer is a view and buy products, features add to cart, and check the status of perfume features purchased. In addition, the website has an added feature that is the discount for booking a certain number of purchases in the form of a package, specific packages with a special price, and ease to choose the delivery services in accordance with customer wishes. As for the admin, there are a variety of features including to input, edit, and delete products, to check the incoming reservations, and see the existing charts. Design and manufacture of the website is done by using the programming language Hypertext Preprocessor (PHP), Ajax, and JavaScript for the manufacture user interface and functional website, and MySQL for database website. Typing and workmanship websites using notepad ++ software.Based on the questionnaire to 10 respondents which samples were taken randomly from customers parfumku.net. Overall with an average score of 80.28% indicates that the website parfumku.net order goods included in either category.